Search for electroweak production of charginos and neutralinos in WH events in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2017)
Results are reported from a search for physics beyond the standard model in proton-proton collision events with a charged lepton (electron or muon), two jets identi fi ed as originating from a bottom quark decay, and signi fi cant imbalance in the transverse momentum. The search was performed using a data sample corresponding to 35.9 fb(-1), collected by the CMS experiment in 2016 at root s = 13 TeV. Events with this signature can arise, for example, from the electroweak production of gauginos, which are predicted in models based on supersymmetry. The event yields observed in data are consistent with the estimated standard model backgrounds. Limits are obtained on the cross sections for chargino-neutralino ((chi) over tilde (+/-)(1) (chi) over tilde (0)(2)) production in a simplified model of supersymmetry with the decays (chi) over tilde (+/-)(1) -> W-(chi) over tilde1(+/-)0 and (chi) over tilde (0)(2) -> H-(chi) over tilde1(0). Values of m((chi) over tilde1 +/-) between 220 and 490 GeV are excluded at 95% confidence level by this search when the (chi) over tilde (0)(1) is massless, and values of m((chi) over tilde 10) are excluded up to 110 GeV for m((chi) over tilde1 +/-) approximate to 450 GeV.